ILOCUTIONARY SPEECH ACTS ON SPECIAL INTERVIEW INDONESIA HEBAT BERSAMA PRESIDEN JOKO WIDODO - Permata Sari, Eva Affiananda; Ekawati, Mursia; Herpindo, Herpindo (Gramatika: Jurnal Ilmiah Kebahasaan dan Kesastraan, 2023)
The study "Ilocutionary Speech Acts on Special Interview Indonesia Hebat Bersama Presiden Joko Widodo" is motivated by the existence of speech acts contained in the interviews which have aims and objectives. The speech does not only telling or informing, but also asking the other party to do something. The purpose of this study was to obtain a description of the types of Ilocutionary Speech Acts on Special Interview Indonesia Hebat Bersama Presiden Joko Widodo. This study uses the method of collecting data observing and note-taking techniques. The method of data analysis uses the matching method followed by the basic technique of sorting out determinants (PUP). The results of this study show that types of illocutionary speech acts, namely (1) assertive speech acts telling, explaining, affirming, and conveying speech acts; (2) directive speech acts asking, appealing, and offering speech acts; (3) commissive speech acts wishes and promises; (4) expressive speech acts congratulating, thanking, praising, hoping, giving thanks, worrying, and caring; and (5) the speech act of declaration is only in the form of deciding speech. The type of speech act that is often found in the Special Interview Indonesia Hebat Bersama Presiden Joko Widodo is the directive asking speech act with 12 data. This study can later be used as input and reference material for linguistic research with pragmatic studies, especially illocutionary speech acts.